Upaya Meningkatkan Kemampuan Kreativitas Melalui Media Loose Parts Pada Anak Usia Dini 5-6 Tahun Di Kober Baiturrahman Karantengah Garut - Marfuatunnisa, Pupun; Kurniawaty, Lia; Hamidah, Agustin (CV. ITTC INDONESIA, 2024)
The purpose of this study is to find out the extent to which the use of Loose Parts media can affect the creativity of Kober Baturrahman children in the learning process so that aspects of child development can be achieved according to their stages. The research method used is Classroom Research. In this study, research was carried out from Pre-Cycle, Cycle 1 and Cycle 2 to determine the growth of creativity using Loose Parts media with a target number of 14 children. Considering the findings of the classroom action research before Cycle 37.9%, Cycle II 61.14% and Cycle II 82.14%, it can be seen that efforts to increase creativity by using the Loose Parts tool have yielded results beyond the predetermined limits.